2017
DOI: 10.1101/127423
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PB-kPRED: knowledge-based prediction of protein backbone conformation using a structural alphabet

Abstract: Libraries of structural prototypes that abstract protein local structures are known as structural alphabets and have proven to be very useful in various aspects of protein structure analyses and predictions. One such library, Protein Blocks (PBs), is composed of 16 standard 5-residues long structural prototypes. This form of analyzing proteins involves drafting its structure as a string of PBs. Thus, predicting the local structure of a protein in terms of protein blocks is a step towards the objective of predi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Kocincová et al [7] observed the spatial differences by visualizing the protein secondary structure and discovered the most varied part of the protein chain, which realized the comparative visualization of the secondary structure. Vetrivel et al [24] used protein blocks to locate and cluster the protein conception space, which generated specific residue submaps.…”
Section: Comparative Visualizationmentioning
confidence: 99%
“…Kocincová et al [7] observed the spatial differences by visualizing the protein secondary structure and discovered the most varied part of the protein chain, which realized the comparative visualization of the secondary structure. Vetrivel et al [24] used protein blocks to locate and cluster the protein conception space, which generated specific residue submaps.…”
Section: Comparative Visualizationmentioning
confidence: 99%